ANALISA PERBANDINGAN DINDING GESER YANG SIMETRIS DAN TIDAK SIMETRIS - Widodo, Theodorus; Pah, Jusuf J.S.; Ninggeding, Aditya Yohanes (Jurnal Teknik Sipil, 2013)
Earthquake make a lateral force on the building. Lateral forces in tall building that exerted in the column is big enough, so need a rigid elements structure such as shear walls to reduce the lateral force. In designing of shear wall, it’s location must be considered carefully, because the placement of shear wall effected on the shear wall symmetry and would lead to eccentricity. The purpose of this study was to compare the symmetrical shear walls and asymmetrical. The method used is thre equivalent static analysis. Using dead load, live load and earthqueke load for loading parameters. This study, using 3 asymmetric shear wall specimens (0.1 b, 0.2 b, and 0.3b) and 1 symmetric shear wall. From the analysis of 3 asymmetric shear wall compared to symmetric shear walls, it is found that the most savely asymmetric shear wall is the shear wall having 0.1 b eccentricity.